A set of sequencing heuristic and the computer code for the TSP. (1999)
This paper proposes a set sequencing heuristic solution for the travelling salesman problem (TSP). It attempts to first select, preferably a set of M smallest elements of the TSP matrix and then form a sequence. A computer code of the procedure was developed in Fortran 77 and used to examine its efficiency and relative effectiveness. It was found to be as effective as, but more efficient than the best of the nearest neighbour heuristics.